Semanda, Metudau, and Tekhang: Marriage and Construction of Ethnic Identity among Belunguh People’s in Tanggamus, Lampung - Nurdin, Bartoven Vivit; Abdulgani, Fuad (Department of Anthropology, Faculty of Social and Political Sciences, Hasanuddin University., 2024)
The Reformation era in Indonesia has resulted in changes in local politics, particularly in relation to ethnic-based groups or adat politics. However, previous studies that have focused on the rise of adat or tradition in local politics have paid limited attention to the dynamics of cultural expression and representation. This article aims to shed light on the reconstruction of ethnic identity among the Belunguh people in Lampung within multiethnic society. To achieve this, an ethnographic inquiry was conducted with the Belunguh people of the Lampung Sai Batin sub-ethnic group, specifically exploring their marriage patterns and rituals. The data collection methods consisted of interview, focus group discussions (FGD), and observation involving twelve informants from traditional leaders (penyimbang adat). The findings of the study highlight the significance of marriage systems and rituals in the construction of Belunguh ethnic identity. While intra-ethnic relations are shaped by marriage practices and rituals of semanda and metudau, the practice of tekhang emerges to facilitate inter-ethnic marriages, particularly with the Javanese. The Belunguh people strive to enhance their awareness of identity by modifying marriage rituals, which reflect their social status, hierarchy, and cultural adaptation in a multiethnic society.